Frequent outpatient attendance among people on the governmental welfare programme in Japan: assessing both patient and supplier characteristics. Issue 10 (19th October 2020) - Nishioka, Daisuke; Saito, Junko; Ueno, Keiko; Kondo, Naoki
Abstract : Objectives: Using linkage data from two municipal public assistance databases and medical assistance claim data, this study aimed to identify characteristics associated with frequent outpatient attendance by people on public assistance, who can access medical care services without copayment in Japan, with simultaneous consideration of supplier factors. Design: We performed a retrospective cohort study. Setting: We used secondary data from the public assistance databases of two suburban municipalities in Japan. Participants: The study population included all adults on public assistance in January 2016, who were observed until December 2016. A total of 6016 people was included in the analysis. Among them, 2956 (49.1%) were men, and 2030 (33.7%) were living alone. Outcome measure: We adopted the definition of frequent outpatient attendance by the Japanese Ministry of Health, Labour and Welfare, visiting the same medical facility 15 times or more in a month for the same health problem. Results: Of 6016 included people, 139 (2.3%) were engaged in frequent outpatient attendance. Multiple Poisson regression showed that, as for the individual factors, the adjusted incidence ratio for frequent outpatient attendance was 1.58 (95% CI 1.05 to 2.39) for people living alone (vs living with others). As for the suppliers, the adjusted incidence ratio for frequent outpatient attendance was 1.74 (95% CI 1.20 to 2.52) for private institutions (vs medical corporations). There were no significant associations between frequent outpatient attendance and individual disability certificate or long-term care needs. Conclusions: This study suggests that among recipients of public assistance who can access medical services without copayment, social isolation may be associated with frequent outpatient attendance. Private clinics may also be associated with this phenomenon. Interventions to prevent social isolation—by for example, providing health and social care in a more integrated manner—may thus be efficacious in reducing the healthcare demands of socially vulnerable individuals.